Longitudinal MRI study over 20 years of cervical posterior extensor muscle area in asymptomatic subjects - Hiroyuki Izumida; Kenshi Daimon; Hitoshi Umezawa; Takehiro Michikawa; Hirokazu Fujiwara; Eijiro Okada; Kenya Nojiri; Hiroyuki Katoh; Kentaro Shimizu; Hiroko Ishihama; Masaya Nakamura; Morio Matsumoto; et al. (Scientific Reports)
Abstract Few studies have investigated long-term changes in the posterior extensor muscles of the cervical spine in healthy subjects. Therefore, we used MRI to investigate changes in the posterior extensor muscles in healthy subjects over 20 years. The subjects of this study were 55 volunteers with an average follow-up period of approximately 20 years. The axial images of the C3/4, C4/5, and C5/6 levels from the initial scan and scans taken 20 years later were evaluated and compared for the following: the cross-sectional areas (CSAs) of the multifidus, semispinalis cervices, semispinalis capitis, and splenius capitis muscles, along with left–right differences, gender differences, influence of age, and muscle fatty degeneration of each muscle. The mean CSAs of the posterior extensor muscles significantly increased at C3/4 and significantly decreased at C5/6 over 20 years. The CSA of posterior cervical extensor muscles always tended to be greater on the left side than on the right side and was significantly larger in men than in women at all levels. The fatty degeneration increased significantly at all intervertebral levels. The decrease in the CSA was significantly associated with smoking status (relative risk: 2.19, 95% confidence interval: 1.32–3.63, p < 0.01), but not with clinical symptoms.